KARAKTERISTIK KEBAHASAAN TOKOH PEREMPUAN DAN LAKI-LAKI DALAM FILM PENDEK - Cahyani, Via; Apriyani, Tristanti (MIMESIS, 2022)
Research is motivated by the differences in the language used by men and women. Environmental factors and society assume that women are gentle creatures, causing women to be careful about the choice of words in speech. Characteristics of women's language coined by Lakoff (1975) became a reference in this study. The problem discussed in this research is how the characteristics of women's language in the short film Reunian and the characteristics of men's language in the short film Dodit Not Penculik. This study aims to describe the linguistic characteristics of women and men in the two short films. The method used in this paper is descriptive qualitative, and quantitative with the subject of the short film Reunian and the short film Dodit Not The Kidnapper. The data acquisition in this study used the method of observing the free-engagement technique and the note-taking technique. Then the analysis in this study is that women tend to be unsure of their speech because women are very concerned about social norms and protect their self-esteem by using more polite speech.